2020
DOI: 10.1016/j.tplants.2020.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Soil Rather Than Xylem Vulnerability Controls Stomatal Response to Drought

Abstract: Trends in Plant Science θ Volumetric water content m 3 m -3 ψ Water potential per volume (water pressure) MPa ψ gs50 Water potential at which stomata close by 50% MPa ψ H50 Water potential at which soil-plant system loses 50% of its conductivity MPa ψ leaf Leaf water potential MPa ψ leaf,predawn Predawn leaf water potential MPa ψ s50 Water potential at which soil loses 50% of its conductivity MPa ψ soil Bulk soil water potential Mpa ψ x50 Water potential at which xylem loses 50% of its maximal conductivity MPa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
190
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 176 publications
(203 citation statements)
references
References 51 publications
11
190
1
1
Order By: Relevance
“…It is widely known that plants sense underground moisture and that these regulatory mechanisms serve to cope with soil moisture variability (Carminati and Javaux 2020;Damour et al 2010;Simonneau et al 1998;Tardieu et al 1992). However, the scientific literature on AMF exerting control on plant moisture reactions has mainly focused on effects in planta while neglecting effects of physical conditioning underground.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely known that plants sense underground moisture and that these regulatory mechanisms serve to cope with soil moisture variability (Carminati and Javaux 2020;Damour et al 2010;Simonneau et al 1998;Tardieu et al 1992). However, the scientific literature on AMF exerting control on plant moisture reactions has mainly focused on effects in planta while neglecting effects of physical conditioning underground.…”
Section: Discussionmentioning
confidence: 99%
“…The series of resistances between the bulk soil, soil–root interface and through the root to the leaf xylem were considered in the soil–plant hydraulic model, assuming that one single root represents all active roots that took up water. A detailed description of the model can be found in Carminati and Javaux (2020), Cai et al (2020), Hayat et al (2020) and supplementary note S1 and Table S1.…”
Section: Methodsmentioning
confidence: 99%
“…Carminati and Javaux (2020) re‐proposed the hydraulic model of Sperry and Love (2015) highlighting the role of soil hydraulic conductance ( K s ). Using a meta‐analysis across species, they showed that the loss of K s , more than the xylem, coincides better with the stomatal closure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After the loss of hydraulic connectivity at the soil-root-interface during prolonged drought (Carminati & Javaux 2020), the amount of internally stored water and its loss via leaky stomata, the cuticle and the bark determine the timing of lethal tissue dehydration (Blackman et al 2016;Choat et al 2018;Duursma et al 2019). Reaching critical desiccation thresholds may thus mark the final step in the dying process of trees rather than being the cause of death.…”
Section: Hydraulic Safety Margins and Non-structural Carbohydratesmentioning
confidence: 99%